Implementation of Christian Education in Early Congregations in the Church: Its Relevance to the Era of Society 5.0 and Christian Learned Wisdom - Sitompul, Baginda; Purba, Aknes Tiorida; Hutabarat, Nunut; Simanjuntak, Michael (LP. Ma'arif Janggan Magetan, 2023)
The implementation of Christian Religious Education in the context of the church, related to the Christian Religious Education of the early church in the Bible, although there are changes regarding the implementation of Christian Religious Education technically, but the principle of Christian Religious Education in the early church remains a reference Christian Religious Education of the current church, for this research discusses the implementation of Christian Religious Education in the early congregations of the church and its relevance to the era of Society 5.0, as well as the importance of learned wisdom in the development of Christian Religious Education and sustainable community development. The history of the early church congregation is also explained, as well as the contribution of Christian Education in shaping character and building society in the era of Society 5.0. This research uses literature method, and the purpose of this study is to provide a comprehensive and integrated view of the Implementation of Christian Religious Education Early Congregational in the Church and its relevance in the era of Society 5.0.